Village Dimensions & Its Legal Instruments (The Challenge Of Creating Prosperous Farmers) - Abustan ABUSTAN (International Journal of Environmental, Sustainability, and Social Science, 2022)
Various programs at the village level will not succeed without understanding from various elements of policy makers and program implementation in the village. This includes government systems, legal and economic instruments, and social/cultural institutions. For this reason, the community service that the author does is to find out various dimensions related to the village and existing legal instruments. The fact is that rural areas are the majority areas with diverse lives. As a supporter of life, the majority of villages produce food, both for household needs and on a larger scale. Although it is the backbone of food producers, it can be said that there has not been much luck and prosperity, due to various factors, including the implementation of policies that have not been in favor of them (farmers). How is the implementation of development in the village after the enactment of Law Number 6 of 2014 concerning Villages as a legal instrument. Are there still gaps and obstacles for farmers? What efforts are made by the state in protecting the citizens (farmers) who live in the village? Community service is carried out to obtain data related to "village autonomy" in the implementation of equitable development. As well as to obtain factual data, the extent to which the village government (stakeholders) are capable of accelerating development acceleration by utilizing the central government development assistance fund (APBN). And, observing the stretching of village development as the front line/lowest level of government in the constitutional system in Indonesia.